2008
DOI: 10.1063/1.2835455
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of electron and hole charge-discharge dynamics in germanium nanocrystal flash memories

Abstract: Electron and hole charge and discharge dynamics are studied on plasma enhanced chemical vapor deposition grown metal-oxide-silicon germanium nanocrystal flash memory devices. Electron and hole charge and discharge currents are observed to differ significantly and depend on annealing conditions chosen for the formation of nanocrystals. At low annealing temperatures, holes are seen to charge slower but to escape faster than electrons. They discharge slower than electrons when annealing temperatures are raised. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
33
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 15 publications
0
33
0
Order By: Relevance
“…2,3 Tailoring particle size can afford control over NC bandgaps by exploiting quantum size effects and is well-established. 4,5 Compositional modifications have also drawn substantial interest for tailoring optoelectronic properties through the incorporation of isovalent elements (e.g., Cd x Zn 1−x Se, 6 CdS x Se 1−x , 7,8 HgSe x S 1−x , 9 CdS x Te 1−x 10 ).…”
Section: ■ Introductionmentioning
confidence: 99%
“…2,3 Tailoring particle size can afford control over NC bandgaps by exploiting quantum size effects and is well-established. 4,5 Compositional modifications have also drawn substantial interest for tailoring optoelectronic properties through the incorporation of isovalent elements (e.g., Cd x Zn 1−x Se, 6 CdS x Se 1−x , 7,8 HgSe x S 1−x , 9 CdS x Te 1−x 10 ).…”
Section: ■ Introductionmentioning
confidence: 99%
“…C-V measurements indicated charge storage in the nc-Ge dots in many recent literatures [102][103][104]. Turan found that the hole loss rate was dramatically reduced by Coulomb blockade from the nc-Ge dots [105]. It has also been observed that very different characteristics were obtained from the nc-Ge dots synthesized with different technologies [106,107].…”
Section: Silicon Nanocrystals Memory Devices and Other Quantum Dot Mementioning
confidence: 88%
“…The use of NCs to study the carriers trapping process has been investigated. [1][2][3][4][5][6][7][8][9] The NCs based memories exhibit many advantages such as insensitivity to local leakage current, weak power dissipation, better endurance, faster speeds of operations, CMOS compatibility, and the possibility of ultimate size reduction. To characterize structures containing NCs, experimental works investigated the macroscopic characterization of the charging effects by the use of standard techniques like as high frequency capacitance-voltage (C-V), 3-9 current-voltage (I-V), 1,2,4,6-8 and current-time (I-t) techniques.…”
mentioning
confidence: 99%